2016
DOI: 10.25311/jkk.vol3.iss2.102
|View full text |Cite
|
Sign up to set email alerts
|

Kejadian Kecacingan pada Siswa Sekolah Dasar Negeri Kecamatan Rumbai Pesisir Pekanbar

Abstract: ABSTRAKPenyakit kecacingan masih menjadi masalah kesehatan. Penyakit ini terutama diderita oleh anak-anak. Pada kondisi kecacingan ringan tidak menimbulkan gejala, pada kondisi berat dapat menimbulkan manifestasi usus, malaise, gangguan perkembangan kognitif, terganggunya perkembangan fisik dan anemia.Penelitian ini bertujuan untuk mengethui proporsi dan faktor-faktor yang berhubungan dengan kejadian kecacingan Soil Transmitted Helminth (STH) yaitu kebiasaan mencuci tangan, kebersihan kuku, ketersediaan jamban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 0 publications
2
14
0
19
Order By: Relevance
“…Nevertheless, it remains necessary the instigation of hand washing with soap as an effort to prevent the disease of worm eggs. This is in line with research (Kartini, 2016), that hand washing is significantly related to the incidence of worm on Elementary School Students. Next to education, employment and washing hands showed no significant relationship statistically with worm infection, although studies conducted by Suhartono (1996) indicates that the knowledge of parents and elementary school students related to worm infection in students.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, it remains necessary the instigation of hand washing with soap as an effort to prevent the disease of worm eggs. This is in line with research (Kartini, 2016), that hand washing is significantly related to the incidence of worm on Elementary School Students. Next to education, employment and washing hands showed no significant relationship statistically with worm infection, although studies conducted by Suhartono (1996) indicates that the knowledge of parents and elementary school students related to worm infection in students.…”
Section: Discussionsupporting
confidence: 79%
“…Kinds of worms that dangerous are roundworms (Ascaris lumbricoides), hookworm (Ancylostoma duodenale and Necutor americanus) and Trichuris trichiura. (Kartini, 2016) STH's infection can give a grave impact on health both directly and indirectly. Directly, STH could affects supply and absorption and food metabolism to human body.…”
Section: )mentioning
confidence: 99%
“…Besides, decreasing nutritious, STH can impede physical growth, intelligence, working productivity, and decrease body's immunity which makes body is susceptible to disease and other infections. (Kartini, 2016) According to data of WHO worms cases in the world are still high where 1 billion people are infected by Ascaris lumbricoides, 795 million are infected by Trichuris trihiura and 740 million are infected by Hookworm. (Mardiana, 2014) While according to data of Health Ministry of Indonesia in 2006, based on survey done by sub-unit diarrhea on 2002 and 2003 in 40 elementary schools in 10 provinces, STH's prevalence is about 2.2%-96.3%.…”
Section: )mentioning
confidence: 99%
“…This can be caused by the presence of worm drug administration activities carried out by Moyudan Community Health Center in elementary school children held in November 2017, which allows at least children infected with helminthiasis. Helminthiasis in elementary school students can be influenced by the consumption of worm medicine in which students who do not take worm medicine within a span of 6 months can risk 11 times greater than students who take worm medicine within a span of 6 months [6].…”
Section: Advances In Health Sciences Research Volume 18mentioning
confidence: 99%
“…The results revealed that the majority of children (95%) defecate carelessly and wash their hands with soil without using soap to wash their hands [19]. During activities such as playing and defecating, the child can touch his fist or the ground containing worm eggs if not washed before eating, it can be swallowed through the hand [6].…”
Section: B the Relationship Between Handwashing Behavior After Bowelmentioning
confidence: 99%